2019
DOI: 10.9734/ajarr/2019/v6i430161
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment for Carcinogenic and Non-carcinogenic Heavy Metal Exposures from Pepper Fruits Cultivated In Katsina State, North West Nigeria

Abstract: This study was conducted to determine the heavy metals concentration in pepper fruits cultivated in Katsina state Nigeria. The objectives were mainly to detect the presence of heavy metals in the cultivated pepper fruits in the study area, compare the concentration of heavy metals in samples in relation to the permissible limits specified by WHO/FAO/USEPA Standards. Samples of the pepper fruits were collected in the year 2017 from the selected area. Analysis for the concentration of these heavy metals; Cr, Cd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
2
1
Order By: Relevance
“…From the Tables (2 and 3) the combined health risks for all the metals in the sample for the adults and children population represented as the HRI were above 1, an indication that the sample is not safe for consumption. The current result is in disagreement to what was previously reported in Katsina State [33][34][35][36][37][38][39].…”
Section: Non-cancer Riskscontrasting
confidence: 99%
See 1 more Smart Citation
“…From the Tables (2 and 3) the combined health risks for all the metals in the sample for the adults and children population represented as the HRI were above 1, an indication that the sample is not safe for consumption. The current result is in disagreement to what was previously reported in Katsina State [33][34][35][36][37][38][39].…”
Section: Non-cancer Riskscontrasting
confidence: 99%
“…The observation that the heavy metals Pb and Fe have values that were higher than the regulatory bodies permissible limits is a pointer that the consumption of sample by the population is not safe because of the potentially high health risk. Also, the mean heavy metals concentrations of the sample was higher than the reported mean heavy metals concentrations in studies that evaluate heavy metals in various food samples that were earlier conducted in Katsina State, Nigeria [33][34][35][36][37][38][39]. The Apparent higher value obtained may not be unconnected with the illegal mining and metal artisanal sites that are located within the vicinity of the sampling area.…”
Section: Heavy Metal Concentrations In Cultivated Lettuce Leavesmentioning
confidence: 54%
“…Although a previous study from Katsina State, Nigeria [8] has reported the heavy metal Ni to be below detection level (BDL) in fish samples, with similar studies conducted in the state in legumes, cereals and vegetables corroborating the same finding [38][39][40][41][42][43]. The present study is among the few of such studies [44,13] that reported a detection of Ni in evaluated food samples.…”
Section: Resultssupporting
confidence: 84%
“…The risk assessment for carcinogenic exposure effect has revealed that the incremental lifetime cancer risk (ILCR) and the cumulative lifetime cancer risks (∑ILCR) were all above the safe limit for cancer in the children population with the heavy metal Ni contributing the highest risk and the sample of the fish sample of Clarias gariepinus having the highest cancer risk (Tables 6). [38][39][40][41][42][43].…”
Section: Resultsmentioning
confidence: 99%